Pengaruh Asimetri Informasi, Siklus Hidup Perusahaan dan Free Cash Flow Terhadap Manajemen Laba Pada Perusahaan Sektor Industri Yang Terdaftar Di BEI Periode 2018-2022 - Alda Firisiah; Ananto, Rangga Putra; Herman, Lisa Amelia (LP2M Politeknik Jambi, 2024)
This study aims to examine the effect of information asymmetry, company life cycle and free cash flow on earnings management. This study was tested with a multiple linear regression model, using the SPSS tool. The population in the study were 34 industrial sector companies listed on the IDX 2018-2022, selected by purposive sampling so that the total sample was 119 data. The data used in this study are the annual financial reports of companies listed on the IDX. Information asymmetry uses bid-ask spread measurements, the company life cycle uses sales growth and free cash flow uses free cash flow measurements. The results of this study prove that information asymmetry and the company life cycle affect earnings management, but free cash flow does not affect earnings management.